2013
DOI: 10.1039/c3ob41221k
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of a non-selective adenosine receptor antagonist into A3-selective high affinity fluorescent probes using peptide-based linkers

Abstract: Advances in fluorescence-based imaging technologies have helped propel the study of real-time biological readouts and analysis across many different areas. In particular the use of fluorescent ligands as chemical tools to study proteins such as G protein-coupled receptors (GPCRs) has received ongoing interest. Methods to improve the efficient chemical synthesis of fluorescent ligands remain of paramount importance to ensure this area of bioanalysis continues to advance. Here we report conversion of the non-sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 26 publications
2
86
0
Order By: Relevance
“…Recent work in our laboratory has focused on the development of fluorescent ligands for the adenosine receptors with improved imaging properties. We found that inclusion of a peptidic linker in an XAC-BODIPY630/650 conjugate improved its affinity and significantly reduced the levels of intracellular non-specific binding (Vernall et al, 2013) compared to a direct XAC-BODIPY630/650 (XAC-X-BY630) conjugate ( Fig. 3) .…”
Section: Required Properties Of a Fluorescent Ligandmentioning
confidence: 92%
See 2 more Smart Citations
“…Recent work in our laboratory has focused on the development of fluorescent ligands for the adenosine receptors with improved imaging properties. We found that inclusion of a peptidic linker in an XAC-BODIPY630/650 conjugate improved its affinity and significantly reduced the levels of intracellular non-specific binding (Vernall et al, 2013) compared to a direct XAC-BODIPY630/650 (XAC-X-BY630) conjugate ( Fig. 3) .…”
Section: Required Properties Of a Fluorescent Ligandmentioning
confidence: 92%
“…Using a fluorescent antagonist that emits at green wavelengths, the assay can be adapted to determine the affinity of fluorescent antagonists emitting at red wavelengths and vice versa (Vernall et al, 2013). Although the throughput of this system is not as high as for FRET or fluorescence polarisation assays (Allen et al, 2000;Veiksina et al, 2014;Zwier et al, 2010), one advantage of this imaging-based technique is the ability to simultaneously determine the affinity and efficacy of an unknown ligand and potentially to correlate this to what is happening at the single cell level.…”
Section: Fluorescent Ligands As Alternatives To Radioligands In Compementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the ligand has to display the necessary receptor subtype selectivity to label the receptor of interest in a cell membrane that may contain other receptors for the same endogenous hormone or neurotransmitter. For example, most cells express multiple adenosine receptors, so it is important to develop highly selective fluorescent ligands for the specific adenosine receptor of interest (Vernall et al, 2013(Vernall et al, , 2014, especially in the context of an entire organism.…”
Section: State Of the Art: Ret Sensorsmentioning
confidence: 99%
“…In an effort to develop a selective A 1 AR uorescent ligand we chose to avoid a xanthine amine congener (XAC)-based pharmacophore because of subtype selectivity concerns as a range of XACuorescent conjugates have been reported as either non AR subtype selective or A 3 AR selective. 7 Cosimelli et al recently reported a series of (benzimidazolyl)isoquinolines as selective antagonists for human A 1 AR (hA 1 AR), among them ligands 1-3 ( Fig. 1), 8 which were used as the inspiration for the uorescent ligand design reported herein.…”
Section: Introductionmentioning
confidence: 99%